Association of frailty with days alive at home in critically ill patients undergoing emergency general surgery: a population-based cohort study. (October 2022) - Alkadri, Jamal; Aucoin, Sylvie D.; McDonald, Bernard; Grubic, Nicholas; McIsaac, Daniel I.
Abstract: Background: Frailty is an established risk factor for morbidity and mortality in older patients undergoing surgery. In people with critical illness before surgery, few data describe patient-centred outcomes. Our objective was to estimate the association of frailty with postoperative days alive at home in older critically ill patients requiring emergency general surgery. Methods: A retrospective population-based cohort study was conducted using linked administrative health data in Ontario, Canada from 2009 to 2019. All individuals aged ≥66 yr with an ICU admission before emergency general surgery were included. We compared the count of days alive at home at 30 and 365 days after surgery based on frailty status using a validated, multidimensional index. Unadjusted and multilevel, multivariable adjusted effect estimates were calculated. A sensitivity analysis based on early recovery category was performed. Results: We identified 7003 eligible patients; 2063 (29.5%) lived with frailty. At 30 days, mean days alive at home with frailty were 4.5 (standard deviation 8.2) and 7.6 (standard deviation 10.2) in those without frailty. In adjusted analysis, frailty was associated with fewer days alive at home at 30 (ratio of means [RoM] 0.68; 95% confidence interval [CI]: 0.60–0.78; P <0.001) and 365 days (RoM 0.72; 95% CI: 0.64–0.82; P <0.001). Individuals with frailty had a higher probability of poor recovery status, with effects increasing across the first postoperative month. Conclusions: In patients with critical illness requiring emergency general surgery, frailty is associated with fewer days alive at home. This information should be discussed with critically ill patients before emergent surgical intervention to better inform decision-making.